2018
DOI: 10.1016/j.jbiomech.2017.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of intervertebral joint forces to center of rotation location and trends along its migration path

Abstract: Translational vertebral motion during functional tasks manifests itself in dynamic loci for center of rotation (COR). A shift of COR affects moment arms of muscles and ligaments; consequently, muscle and joint forces are altered. Based on posture- and level-specific trends of COR migration revealed by in vivo dynamic radiography during functional activities, it was postulated that the instantaneous COR location for a particular joint is optimized in order to minimize the joint reaction forces. A musculoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Ghezelbash et al (2015) found low to moderate impact on model predictions and suggested that intervertebral translational DoFs can be ignored for small trunk angles in flexion. Furthermore, Senteler et al (2018) investigated the sensitivity of disc force predictions to center of rotation (COR) locations. They asserted that a posterior COR in an upright position and an anterior COR in flexion would optimize the lumbar joint loads.…”
Section: Discussionmentioning
confidence: 99%
“…Ghezelbash et al (2015) found low to moderate impact on model predictions and suggested that intervertebral translational DoFs can be ignored for small trunk angles in flexion. Furthermore, Senteler et al (2018) investigated the sensitivity of disc force predictions to center of rotation (COR) locations. They asserted that a posterior COR in an upright position and an anterior COR in flexion would optimize the lumbar joint loads.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the herein introduced concept of confidence ellipses may be utilized to assess the influence of model parameter changes (sensitivities) on the centrode location. These investigations could include the influence of ligament stiffness or failure (Abouhossein et al 2013;Alapan et al 2013;Putzer et al 2016), joint forces (Senteler et al 2017), implant positioning (Dreischarf et al 2015;Rohlmann et al 2010) or variable load application (Rohlmann et al 2009b).…”
Section: On Torque-driven Experiments and Physiological Insightsmentioning
confidence: 99%
“…First, the location of the centrode across individual spine geometries was calculated, both with and without preload representing the upper body weight. This individualized modeling is particularly worthwhile, since, on the one side, modelers from MBS and finite element (FE) communities usually employ generic models (Abouhossein et al 2013;Qiu et al 2003;Senteler et al 2017;Schmidt et al 2008), which cannot account for structure-based deviations. Experimenters, on the other side, conduct helpful individual measurements, but have no elaborated model on hand (Cossette et al 1971;Gertzbein et al 1985;Haher et al 1991;Niosi et al 2006;Ogston et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…35 The ability of the COR to be resolvable into these parameters can be used to characterize/quantify the kinematic features of the lumbar spine and specific motion segments. 36,37 The use of COR location and migration paths therefore lends itself to a greater utility than its constituent parameters when evaluating lumbar spine and motion segment kinematics as well as intersegmental conditions. Many studies have investigated the CORs of the human lumbar spine under various conditions (e.g.…”
Section: 24mentioning
confidence: 99%